(untitled) (Revista Lusófona de Educação, 2025)
This study examines the perspectives of recently graduated teachers qualified to teach in the first and second cycles of basic education regarding the training received in their master’s programme. Based on interviews with 37 participants, the findings reveal an ambivalent assessment: although they express overall satisfaction, they identify more weaknesses than strengths. Among the valued aspects, the curricular units of supervised teaching practice and didactics stand out; criticisms include insufficient preparation for practice, content repetition, weak integration between theory and practice, excessive coursework, and lack of feedback. Suggestions for improvement include longer internships, closer alignment with school realities, and a reorganisation of training strategies. The findings highlight the need for a more integrated, reflective teacher education aligned with the demands of professional practice. Keywords: Initial teacher education; Perceptions; Theory-practice relationship